Podstawy Projektowania Jednonawowych Sprężonych Ram Wielopiętrowych - Paprocka-Grabczyńska, W. (Engineering Transactions, 1965)
This paper presents a solution of the problem of design of a single-bay multi-storey prestressed frame of an element most commonly met with in prestressed multi-storey buildings. The final static systems of this structure and the intermediate ones through which the structure passes during assemblage are discussed. The author’s method for determining the internal forces produced by loads applied in the course of construction, presented in her paper «A single-stage computation method of multi-storey frames, taking into account changes of the static system during the assemblage of the structure» [Rozpr. Inzyn., 2, 10 (1962)] is described in brief. The discussion includes load systems replacing the prestress. Particular states of loading are analysed as well as their validity criteria and methods for selecting cross-sections and prestressing forces. Finally the problem of cable location design is solved by means of a method based on limit envelopes of the pressure lines due to prestressing making use of tables of internal forces for k storey of the frame. Directions for design are given.